Pemodelan Perilaku Tegangan dan Regangan Beton pada Suhu Tinggi dengan Software LUSAS - Suryanita, Reni; Rahmadhan, Wahyu; Kamaldi, Alfian (Department of Civil Engineering, Diponegoro University, 2019)
The concrete structure exposed to high temperatures can affect the strength of the structure. Limitations in the experimental method can be solved by mathematical modeling. This study aims to identify the stress and strain behavior that occurs at high-temperatures. The model is a cylindrical concrete with a diameter of 150 mm and a height of 300 mm. The concrete strength design is 25 MPa. The temperatures of the model are 100 °C, 200 °C, 300 °C, 400 °C, 500 °C, 600 °C, and 700 °C. The model analysis using LUSAS v. 16 Software to observe the properties of the concrete material due to exposure to high temperatures. The results of the study get the higher the temperature received by concrete, the strength of the concrete decreases. Concrete that burned to a temperature of 300 °C still had 82% available power, and at a temperature of 700 °C, the remaining concrete strength was 30%. The strain increases to 423% from normal conditions at a temperature of 700 ° C. Therefore, the results of the study can be used as a reference for structural engineers to know the behavior of the concrete that exposure to high temperatures.